Late Miocene Exhumation of the Western Cordillera, Ecuador, Driven by Increased Coupling Between the Subducting Carnegie Ridge and the South American Continent. Issue 1 (12th January 2023) - Margirier, Audrey; Strecker, Manfred R.; Reiners, Peter W.; Thomson, Stuart N.; Casado, Ismael; George, Sarah W. M.; Alvarado, Alexandra
Abstract: The subduction of bathymetric highs, such as aseismic ridges, leads to far‐reaching changes in the dynamics of subduction zones with increased plate coupling and deformation in the upper plate. Subduction of the submarine Carnegie Ridge on the Nazca Plate has fundamentally impacted late Cenozoic magmatism and tectonic activity in the northern Andes. However, the timing of onset of Carnegie Ridge subduction has been a matter of debate. Time‐temperature inverse modeling of new thermochronological data from the Western Cordillera of Ecuador reveals two phases of cooling separated by isothermal conditions. The first cooling phase postdates early and middle Miocene magmatism in the Western Cordillera and is attributed to post‐magmatic thermal relaxation. The second cooling phase started after 6 Ma. Inferred to record the onset of tectonically controlled rock uplift and exhumation in the Western Cordillera, this phase is coeval with the last cooling phase recorded in the Eastern Cordillera. Based on these findings, we suggest that the onset of subduction of the Carnegie Ridge at ∼6–5 Ma increased plate coupling at the subduction interface, promoting shortening, regional rock uplift, and exhumation in the northern Andes. Overall, our results highlight the essential role of bathymetric highs in driving regional upper‐plate deformation at non‐collisional convergent plate margins. Plain Language Summary: Topographic growth and morphology of the Andes have been influenced by subduction processes, tectonic inheritance, and climate. Here, we investigate the role of subduction of high topography on the ocean floor in driving deformation in the upper plate at the Nazca‐South America ocean‐continent plate margin. The subduction of the Carnegie Ridge, a linear, topographically high sector on the Nazca Plate, has impacted magmatism and deformation processes in the Ecuadorian Andes. However, the timing of onset of ridge subduction is debated. We employed radioisotopic dating techniques to evaluate the uplift of the Andes. These techniques record the cooling of rocks as mountain ranges are uplifted and eroded. The thermal histories of rocks from the Western Cordillera in Ecuador reveal two distinct cooling phases. The first cooling phase occurred shortly after Miocene magmatic bodies were emplaced in the Western Cordillera. The second cooling phase began at ∼6–5 Ma, coeval with the last cooling phase in the Eastern Cordillera. We attribute this cooling phase to the onset of uplift and erosion in the Western Cordillera. Based on these findings, we suggest that the onset of subduction of the Carnegie Ridge increased plate coupling and promoted shortening and rock uplift in the northern Andes. Key Points: Thermochronological data reveal two cooling phases in the Western Cordillera of Ecuador, during the Miocene and after 6 Ma The onset of cooling at 6 Ma was associated with shortening, rock uplift, and exhumation in the Western Cordillera Mio‐Pliocene exhumation was related to stronger coupling of the subduction interface due to the initial subduction of the Carnegie Ridge